How Islamic Capital Market Literacy, Knowledge of SOTS, and Religiosity Influence Perceived Risk: The Mediating Role of Perceived Sharia Compliance - Dini Queentasari; Megawati Simanjuntak; Nur Hasanah (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The Islamic capital market is essential in Indonesia’s financial system, driven by a growing demand for Sharia-compliant financing and related financial products. Despite investor participation is currently below its potential, the market holds promising future growth.Purpose: This study investigates the effects of Islamic capital market literacy, knowledge of the Sharia online trading system (SOTS), and religiosity on perceived risk, emphasizing the mediating role of perceived Sharia compliance in lowering the perceived risk in investing in the Islamic capital market.Design/methodology/approach: Data from 294 Indonesian Muslims aged 18-49 without prior experience using Sharia online trading system (SOTS) were analyzed using multiple linear and hierarchical regression analyses.Findings/Result: Regression analysis results indicate that Islamic capital market literacy significantly lowers perceived risk, while knowledge of SOTS and religiosity do not have a significant individual effect. Interestingly, when combined, Islamic capital market literacy, knowledge of SOTS, and religiosity collectively lower perceived risk. The regression model explains 16.8 percent of the variance in perceived risk. Furthermore, perceived Sharia compliance is a mediating factor that strengthens the collective effect of these three factors on perceived risk. This interaction explains 25.4 percent of the variance in perceived risk, emphasizing the importance of enhancing perceived Sharia compliance to strengthen the collective effect of Islamic capital market literacy, knowledge of SOTS, and religiosity on the perceived risk of Sharia-compliant investments within the Islamic capital market. Conclusion: most respondents have a positive perceived Sharia compliance, with the highest positive response related to the periodic evaluation and delisting non-compliant stocks. In contrast, the lowest positive response was related to the effectiveness of the Sharia Online Trading System (SOTS) in preventing violations of Sharia principles and the criteria used to establish Sharia compliance.Originality/value (State of the art): Unlike prior studies that examine literacy, religiosity, or SOTS knowledge separately, this study demonstrates that perceived Sharia compliance is the key mechanism that enables these factors to jointly reduce perceived risk. This finding reframes perceived risk in the Islamic capital market as a collective and compliance-driven construct rather than the outcome of isolated individual factors. Keywords:   islamic capital market literacy, knowledge of SOTS, perceived risk, perceived sharia compliance, religiosity